(untitled) (Research, Society and Development, 2024)
Objective: The objective of the present study is to report a clinical case of peri-implantitis in which the lack of oral hygiene represented a decisive factor in the loss of one of the previously installed implants. Method: This is a case study, using a qualitative approach, as the object of study is the result and element under investigation. Results and Discussion: After undergoing an implant, the patient developed an infection with purulent secretion in the peri-implant region, after the procedure, the patient sought the service complaining of pain, follow-up was carried out and subsequently cleaning procedures with antiseptic and after Integrated Bone Regeneration (ROG), there was loss of a tooth and reversal of the inflammatory process. Conclusion: Incomplete surface decontamination appears to be the biggest obstacle to new bone formation on the previously exposed surface of the implant. From what was observed, it can be concluded that biofilm control maintains the health of the soft tissue-implant interface, and there is a relationship between the presence of biofilm and inflammation of the tissues around the implants.